Perilaku petani terhadap risiko usahatani di lahan pantai kabupaten kulon progo =The farmer behavior toward risksthe farming in shore land kulon progo regency - Juarini Juarini; Sri Widodo; Masyhuri Masyhuri; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2002)
The research aims to know : (1) the risk of farm price and production of the shore land, (2) the farmer behavior toward risks of shore land farming,- (3) factors affecting the farmer behavior toward risks, (4) the relation between risks with expected return.The research was carried out at the shore land of Kulon Progo Regency. sub district Panjatan. There were 408 farm fields those were farmed with four combination of irrigation technology and plants : Pump-Chilli, Pump-Watermelon, Pump Chilli-Watermelon and Dipper-Chilli. These were taken 120 farm fields/farm household as sample.s proportionally in accordance to each combinations. Variation coefficient, Regression analysis and MOTAD Programming were used in the analysis.The analysis shows that : (I) chili has higher price risk than watermelon, fi-titers with Pump-Chilli to face highest production risk, (2) most farmers is risk averse in shore land farming, (3) the farmer behavior toward risks was affected by experience of farmers, family members, planting month, and cropping pattern , and (4) the higher of the risks the greater of the expected net return and reverse. Face the risks, the farmers lend to diversified.